The effects of hypocaloric, high-protein diets on cardiovascular risk factors and weight loss in obese adults: a systematic review - Martin Lauran; Ali Moghadas Jafari; Kosar Mohamed Ali; Seyed Mostafa Hosseini (Journal of Biostatistics and Epidemiology)
Background: This systematic review has been undertaken in order to assess the effects of hypocaloric, high-protein diets on weight loss and cardiovascular risk factors such as serum lipid levels in metabolically healthy obese adults. The primary outcomes measured include changes in pre- and post- diet mean BMI, LDL-C, HDL-C, TAG, and TC levels. Method: Four databases including: Embase, MEDLINE (via PubMed), Cochrane and Web of Science were searched with no restrictions on language or publication period. Clinicaltrials.gov was also searched in order to identify unpublished or on-going studies. Results: Three of four studies included in this systematic review noted a significantly greater loss in pre- and post- diet mean BMI levels in the hypocaloric, high-protein diet group as compared to hypocaloric, non-high protein diets (control). Whilst pre- and post-diet mean LDL-C, HDL-C, TAG, and TC levels did not differ significantly among hypocaloric, high-protein and control diet groups. Conclusion: Hypocaloric, high-protein diets had an unclear effect on blood-lipid levels as compared to control. Weight loss however was significantly greater in the hypocaloric, high-protein group as compared to other hypocaloric, non-high-protein diet groups.